Development and validation of an HPLC method for the quantification of strychnine in Strychnos wallichiana Steud. ex DC. - Nguyen, Viet Khan; Truong, Tieu Bang; Le, Anh Khoa; Chu, Thi Huong; Dao, Thi Cam Minh (Tạp chí Y Dược Huế, 2026)
Abstract Background: Strychnos wallichiana Steud. ex DC. is a medicinal plant, in which strychnine exhibits strong biological activity but also carries high toxicity. Accurate quantification of strychnine in this medicinal plant is essential to ensure safe usage, particularly in research and medical applications. The objective of this study is to develop and validate a method for the quantification of strychnine in S. wallichiana using HPLC. Materials and methods: S. wallichiana samples were collected from Nghe An province. Strychnine was extracted from the plant material and analyzed using high-performance liquid chromatography (HPLC). Method validation was performed in accordance with analytical guidelines. Results: The chromatographic conditions include an ACN:buffer system (H3PO4 0.3% + (C2H5)3N 0.2%) in a 12:88 ratio and a flow rate of 0.5 mL/min on an InertSustain™ C18 column (4.6 x 250 mm; 5 μm), and a detection wavelength of 263 nm. The analytical method demonstrated system suitability and high specificity, with a wide linear range and reliable accuracy and precision. Conclusion: The developed HPLC method meets the required standards for the quantification of strychnine in S. wallichiana medicinal plant material.